Reflective groups about gender for men in the virtual environment - first adaptations, methodological challenges and potentialities - Beiras, Adriano (2021)
This article discusses the adaptation of gender reflective group methodologies to an online system, by programs that have the potential for meetings in the virtual space. We report some challenges, such as, maintaining a theoretical-philosophical and methodological stance that are aligned with the reflective processes, and the co-construction of a relational discussion space. Creating scenarios where there is respect for diversity and the problematization of gender relations and that are attentive to a new social context and the possibility(dangers) of the production of new inequalities. We add to the discussion, some adaptations to the initial process and some challenges and potentialities that were faced in the implementation of these groups in the initial months of social isolation due to the pandemic. Considering the experience of using the methodology of reflective groups from the Noos Institute and the MEMOH organization, that are especially focused on men that are interested in a collective reflection on gender and masculinities. A new form of coexistence and relational etiquette is developed that allows advances, but also aligns some losses, if compared to the presencial format.